First-year medical students’ perceptions of a self-regulated learning-informed intervention: an exploratory study - Taylor Boyd; Henrike Besche; Richard Goldhammer; Afaf Alblooshi; Bradley I. Coleman (BMC Medical Education, 2022)
Abstract Background Students with developed self-regulated learning (SRL) skills demonstrate an ability to set individualized educational goals, select optimal learning strategies for reaching these goals, and reflect on overall progress. The primary aims of this study were to investigate first-year medical students’ perceived utility of a self-regulated learning-informed intervention and to assess the impact of its implementation on students’ intended use of SRL throughout medical school. Methods A two-part educational intervention focused on SRL skill development was carried out at Harvard Medical School during the start of the 2021 academic year. For the first component of the intervention, 169 first-year medical students engaged in an interactive class session structured around SRL concept videos, a brief lecture, small group discussions and individual reflection. Students completed pre- and post-intervention surveys which inquired about learners’ current and anticipated application of SRL skills. During the second component of the intervention, 15 first-year medical students participated in a set of one-on-one academic SRL coaching sessions. All coaching participants completed follow-up semi-structured interviews. Results A statistically significant increase was observed between students’ use of skills in all domains of self-regulated learning prior to the intervention and their anticipated use of these skills following the intervention. Prior to the intervention, 60.1% (n = 92) of students reported utilizing evidence-based learning strategies, compared to 92.8% (n = 142) of students (p < 0.001) who anticipated applying this SRL skills at the completion of the classroom session. Six core themes emerged from qualitative analysis of the post-intervention survey including learning plan development, accountability and progress tracking, goals for growth, engagement through active learning, routine reflection, and adapting to the curriculum. Conclusions Both classroom-based learning sessions and one-on-one academic coaching programs are feasible approaches for encouraging the use of self-regulated learning techniques in the preclinical setting.